Solar power inverter - Mohd Hafizuddin, Mohamed Ariffin (2013)
The solar power inverter is the one of the critical component in a solar system that has been developed. It is highlights the aspects of power electronic packaging concerning functional and packaging integration in solar inverter technology. Basically, it performs the conversion of the variable DC output of the Photovoltaic (PV) module(s) into a clean sinusoidal 50- or 60 Hz AC current that is then applied directly to the commercial electrical grid or to a local, off-grid electrical network. Communication capability is also included so that the user can control or monitor the inverter. The user also can report on power and operating conditions provide firmware updates and control the inverter grid connection. For systems with battery energy storage, the controller can control the charging as well as switch over to battery power once the sun sets or cloud cover reduces the PV output power. The controller executes the very precise algorithms required to invert the DC voltage generated by the solar module into AC This controller is programmed to perform the control loops necessary for all the power management functions necessary including DC/DC and DC/AC.